Degradation and Detection of Endocrine Disruptors by Laccase-Mimetic Polyoxometalates - Chen, Kun; Liu, Shengqiu; Zhang, Qiongyu (Frontiers in Chemistry, 2022)
Endocrine disruptors are newly identified water contaminants and immediately caught worldwide concern. An effort has been made to degrade endocrine disruptors in the water body by relying on laccase-assisted approaches, including laccase-mediated catalytic systems, immobilized laccase catalytic systems, and nano-catalytic systems based on atypical protein enzymes. Analogous to laccases, polyoxometalates (POMs) have a similar size as these enzymes. They are also capable of using oxygen as an electron acceptor, which could assist the removal of endocrine disruptors in water. This perspective begins with a brief introduction to endocrine disruptors and laccases, summarizes current approaches employing laccases, and focuses on the nano-catalytic systems that mimic the function of laccases. Among the inorganic nanoparticles, POMs meet the design requirements and are easy for large-scale production. The catalytic performance of POMs in water treatment is highlighted, and an example of using polyoxovanadates for endocrine disruptor degradation is given at the end of this perspective. Exploring laccase-mimetic POMs will give key insights into the degradation of emergent water contaminants.